Ion Vinea între modernitate şi avangardă - Laurenţiu Hanganu (Revista de Istorie și Teorie Literară)
The study discusses Ion Vinea’s status and personality against the background of the Romanian literature of the 20th century. Presented by some important critics (E. Lovinescu, S. Cioculescu) as an “extremist” writer, on the one hand, accused by the members of the avant-garde movement, on the other hand, that he hesitated to reject the cultural tradition, as a whole Ion Vinea appears to have an unstable and curious position. But when truly analysed, his work proves to be “highly modernist” – being one of the most representative in the process of the Romanian literature’s modernisation.